2013
DOI: 10.1523/jneurosci.0679-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Insulin-Like Peptide in Long-Term Synaptic Plasticity and Long-Term Memory of the Pond SnailLymnaea stagnalis

Abstract: The pond snail Lymnaea stagnalis is capable of learning taste aversion and consolidating this learning into long-term memory (LTM) that is called conditioned taste aversion (CTA). Previous studies showed that some molluscan insulin-related peptides (MIPs) were upregulated in snails exhibiting CTA. We thus hypothesized that MIPs play an important role in neurons underlying the CTA-LTM consolidation process. To examine this hypothesis, we first observed the distribution of MIP II, a major peptide of MIPs, and MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 82 publications
4
71
0
Order By: Relevance
“…More recently, Murakami et al (2013) examined the effects of insulin on CTA-LTM, and found that insulin acted at a synaptic connection in the neural circuit underlying CTA-LTM. We then further hypothesized that the change in hemolymph glucose concentration was caused by a rise in the insulin concentration (insulin spike) triggered by the CS (sucrose to the lips) during the course of taste aversion training (Mita et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Murakami et al (2013) examined the effects of insulin on CTA-LTM, and found that insulin acted at a synaptic connection in the neural circuit underlying CTA-LTM. We then further hypothesized that the change in hemolymph glucose concentration was caused by a rise in the insulin concentration (insulin spike) triggered by the CS (sucrose to the lips) during the course of taste aversion training (Mita et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…day 13 snails). We have previously showed that the injection of an insulin receptor antibody to the isolated central nervous system (CNS) blocked the long-term enhancement of synaptic connections in the feeding circuitry underlying CTA-LTM (Murakami et al, 2013;Mita et al, 2014a,b). We therefore trained day 5 snails by a taste aversion protocol.…”
Section: Insulin Effects In Severely Food-deprived Snailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that molluscan insulin-related peptides (MIPs) were upregulated in snails exhibiting CTA (Azami et al, 2006). More recently, we have shown at the electrophysiological level that application of mammalian insulin or MIPs to the isolated central nervous system (CNS) evoked long-term synaptic enhancement at the serotonergic excitatory monosynaptic connection between the cerebral giant cell (CGC) and the buccal 1 (B1) motor neuron (Murakami et al, 2013). That is, the excitatory postsynaptic potentials (EPSPs) recorded in the B1 motor neuron elicited by activation of the CGC were significantly increased when insulin was applied to the CNS.…”
Section: Introductionmentioning
confidence: 99%